Static and Dynamic Response of Curved Concrete Frame Structures (Case Study: Jakarta International Stadium) - Sanjaya, Arif; Sukamdo, Pariatmono (Universitas Mercu Buana, 2024)
An ideally designed building should be symmetrical to mitigate eccentricities between the center of mass and the center of stiffness during seismic events. However, suppose a special design is intended to enhance the aesthetics and visual appeal of a building. In that case, it should still be engineered to perform well in static and dynamic behaviours. Jakarta International Stadium is an example of a building with a circular shape, irregular vertical geometry, and lacks expansion joints. This research investigated the static and dynamic behaviours of four structural models: the entire building without expansion joints (model ND) andthe building with expansion joints (models D1, D2, and D3). The analysis included internal forces, mode shape analysis, structural displacements, inter-story drifts, and base shear forces. The analysis is conducted using the SAP2000 v22 software. The analysis results indicated that the models with expansion joints in Jakarta International Stadium generally exhibit several positive effects. These included reducing structural displacements, inter-story drifts, internal forces, and base shear forces. Furthermore, all modalities remain within the standard limits SNI 1726-2019 set.